THE PORTRAYAL OF POST TRAUMATIC STRESS DISORDER AS SEEN IN THE MAIN CHARACTER IN THE WOMAN IN THE WINDOW NOVEL - Fadhilah Salma Husna; Heri Kuswoyo (Linguistics and Literature Students' Journal, 2022)
This study discussed the post-traumatic stress disorder (PTSD) experienced by Anna Fox in the novel The Woman in The Window by A.J Finn. This study aims to investigate the causes and analyze the impact that occurs by finding the symptoms experienced by Anna Fox. Post-traumatic stress disorder theory to analyze the behavior data and character condition was applied. This study used a psychological approach. In addition, this analysis used a qualitative descriptive method to describe the problem using words. From this study, three findings can be clarified as the problem formulation, namely (1) two causes of Anna's post-traumatic stress disorder, (2) symptom re-experiencing, avoidance, mood and cognition, and arousal activity symptoms, and (3) the impacts of post-traumatic stress disorder suffered by Anna based on physical, emotional, mental, behavioral, and spiritual aspects.Keywords: Main character, post-traumatic stress disorder, psychological Approach, The Woman in The Window